Effect of cross-linking with Aloe vera gel on surface and physicochemical properties of edible films made from plantain flour - Gutiérrez Carmona, Tomy José (2016)
Films made from plantain flour with incorporation of different concentrations (0, 2, 4 and 6 %) of a natural filler (Aloe vera gel - Av gel) were obtained by the casting method. The aim of this paper was to characterize the surface and physicochemical properties on plantain flour edible films. The average molecular weight, moisture, infrared spectroscopy, contact angle and mechanical properties were determined. Also, microstructural characterization was performed by atomic force microscopy and scanning electron microscopy. The Av gel produced cross-linking on the starch that is found in plantain flour, resulting in films with the following characteristics: smoother, more transparent, more rigid and plastics, less moist and with more hydrophobic surfaces. Finally, the surface properties of these materials were defined by the surface energy of material, which depends on the intermolecular interactions such as van der Waals-type interactions (hydrogen bond) and new bonds (cross-linking) formed between biopolymeric chains (plantain flour).